Structural Basis for Allostery in PLP-dependent Enzymes - Tran, Jenny U.; Brown, Breann L. (Frontiers in Molecular Biosciences, 2022)
Pyridoxal 5’-phosphate (PLP)-dependent enzymes are found ubiquitously in nature and are involved in a variety of biological pathways from natural product synthesis to amino acid and glucose metabolism. The first structure of a PLP-dependent enzyme was reported over 40 years ago, and since that time, there is a steady wealth of structural and functional information revealed for a wide array of these enzymes. A functional mechanism that is gaining more appreciation due to its relevance in drug design is that of protein allostery, where binding of a protein or ligand at a distal site influences the structure, organization, and function at the active site. Here, we present a review of current structure-based mechanisms of allostery for select members of each PLP-dependent enzyme family. Knowledge of these mechanisms may have a larger potential for identifying key similarities and differences among enzyme families that can eventually be exploited for therapeutic development.